Can Virtual Reality be Used for the Prevention of Peer Sexual Harassment in Adolescence? First Evaluation of the Virtual-PRO Program - Sánchez-Jiménez, Virginia; Rodríguez-de Arriba, María Luisa; Ortega-Rivera, Javier; Muñoz-Fernández, Noelia (Intervención psicosocial, 2024)
The present study analyzed the Virtual-PRO program's efficacy in preventing peer sexual harassment by promoting the bystanders' active intervention and incorporating a virtual reality (VR) component. The impact of the program on sexist attitudes, moral disengagement, the intention to intervene as bystanders, and the involvement in sexual aggression and victimization was tested. Virtual-PRO is a VR-enhanced sexual harassment curricular prevention program of six one-hour sessions. The evaluation comprised a pre-test, a post-test after the intervention, and a follow-up measure at three months. In the study, 579 Spanish adolescent students aged between 12 and 17 years ( = 14.76, = 0.88; 47.1% boys) were randomly grouped into experimental ( = 286) and control ( = 293) conditions. The Virtual-PRO program effectively controlled participants' levels of sexism and reduced moral disengagement in the experimental group compared to the control group three months after the intervention. The program also showed positive results in changing bystander behavior, increasing the intention to intervene when the victim was not a friend. Finally, visual/verbal and online victimization decreased in the experimental group and increased in the control group. No differences were found for physical sexual victimization and sexual aggression. The first trial of the Virtual-PRO program is promising and highlights the use of VR as a sexual harassment prevention tool. Follow-up measures are essential to determine the impact of interventions accurately.